Primary School Teachers’ Awareness and Experiences in Addressing Environmental Challenges in Tanzania: The Case of Dar es Salaam and Kilimanjaro Regions - Raphael Kimaro, Aurelia (Tanzania Journal for Population studies and Development, 2026)
This study examines the awareness and experiences of primary school teachers in Tanzania concerning environmental changes and challenges. The fundamental research question was to explore the extent to which teachers understand local and global environmental issues and their implications. Using the grounded theory and thematic analysis, interviews with 24 teachers from five schools in the study area revealed that environmental changes are predominantly driven by anthropogenic activities; and are exacerbated by poverty, deforestation, and climate variability. Teachers identified rising temperatures, biodiversity losses, waste mismanagement, and pollution as the key concerns. The findings underscore the necessity for capacity building among educators, reforms in environmental education curricula, and government interventions to combat poverty and promote sustainability. Based on their experience, primary school teachers recommended strengthening environmental education in primary schools, fostering community-led conservation initiatives, and addressing socio-economic barriers to sustainable development. This study contributes to the understanding of the critical role of teachers in addressing Tanzania ’s environmental challenges, and shaping future generations towards ecological stewardship.